Teratogen exposure and congenital ocular abnormalities in Brazilian patients with Möbius sequence - Ventura, Camila Vieira Oliveira Carvalho (2014)
Purpose: To assess the sociodemographic profiles, teratogen exposures, and ocular congenital abnormalities in Brazilian patients with Möbius sequence. Method: Forty-four patients were recruited from the Brazilian Möbius Sequence Society. This cross-section comprised 41 patients (age, mean ± standard deviation, 9.0 ± 5.5 years) who fulfilled the inclusion criteria. The parent or caregiver answered a questionnaire regarding sociodemographic data and pregnancy history. Patients underwent ophthalmological assessments. They were subdivided into groups according to misoprostol exposure during pregnancy, and the two groups were compared. Results: Mothers/caregivers reported unplanned pregnancies in 36 (88%) cases. Of these, 19 (53%) used misoprostol during their first trimesters. A stable marital status tended to be more frequent in the unexposed group (P=0.051). Incomplete elementary school education was reported by two (11%) mothers in the exposed group and by three (14%) mothers in the unexposed group (P=0.538). The mothers' gestational exposures to cocaine, marijuana, alcohol, and cigarettes were similar in both groups (P=0.297, P=0.297, P=0.428, and P=0.444, respectively). One (5%) case of Rubella infection during pregnancy was found in the unexposed group. The main malformations in the exposed and unexposed groups were the following: strabismus (72% and 77%, respectively), lack of emotional tearing (47% and 36%, respectively), and lagophthalmos (32% and 41%, respectively). Conclusion: Stable marital statuses tended to be more frequent among mothers that did not take misoprostol during pregnancy. Exposures to other teratogens and the main ocular abnormalities were similar in both groups.